1998
DOI: 10.1007/s004420050420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevation on sexual reproduction in alpine populations of Saxifraga oppositifolia (Saxifragaceae)

Abstract: Self-compatibility in high arctic and alpine areas is regarded as an adaptation to low pollinator abundance. However, high genetic variability as a consequence of outcrossing is, with regard to population persistence, favorable in highly stochastic environments such as tundra habitats. To evaluate these contradictory scenarios, I performed in situ pollination experiments to examine the breeding system of the predominant outcrosser Saxifraga oppositifolia in ten populations at two different elevations in the Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 40 publications
3
55
1
1
Order By: Relevance
“…Totland 2001), and outbreeding is the dominant breeding system in long-lived species (e.g. Arroyo and Squeo 1990;Gugerli 1998). It thus would be of great interest to learn whether lizard effects are found in other high mountain areas in the world, and study its repercussions at the level of community structure.…”
Section: Discussionmentioning
confidence: 99%
“…Totland 2001), and outbreeding is the dominant breeding system in long-lived species (e.g. Arroyo and Squeo 1990;Gugerli 1998). It thus would be of great interest to learn whether lizard effects are found in other high mountain areas in the world, and study its repercussions at the level of community structure.…”
Section: Discussionmentioning
confidence: 99%
“…In the central to southern European high mountains, S. oppositifolia is diploid (2n = 26), at least within its Alpine distribution (Küpfer and Rais 1983;Kaplan 1995), and reproduces mainly by cross-pollination through dayflying butterflies and flies (Stenström and Molau 1992;Heß 2001), although selfing is possible (Gugerli 1997(Gugerli , 1998. The species has a wide ecological tolerance, especially in relation to altitude (temperature), soil type and water availability.…”
Section: Study Speciesmentioning
confidence: 99%
“…Arctic and alpine organisms cope with extreme environments with specialized life history strategies, and a suite of other biochemical, morphological, and behavioral adaptations (Martin 2001;Martin and Wiebe 2004). Studies along environmental gradients have shown that offspring number, offspring size, and adult survival often covary with latitude or altitude in plants (Eriksen et al 1993;Gugerli 1998), invertebrates (Mani 1968;Blanckenhorn 1997;Baur and Baur 1998), and terrestrial vertebrates (Berven 1982;Dobson 1992;Krementz and Handford 1984). Arctic and alpine organisms are often long-lived and may be some of the most effective sentinel species for detecting biological responses to environmental change (Morris and Doak 1998;Inouye et al 2000; Barbraud and Weimerskirch 2001;Cooch et al 2001;Derocher et al 2004).…”
Section: Introductionmentioning
confidence: 99%